Distinctive Distribution of Secretory Phospholipases A2 in the Venoms of Afro-Asian Cobras (Subgenus: Naja, Afronaja, Boulengerina and Uraeus) - Tan, Choo Hock; Wong, Kin Ying; Tan, Nget Hong; Ng, Tzu Shan; Tan, Kae Yi (MDPI, 2019)
The protein abundances of phospholipases A2 in cobra venom proteomes appear to vary among cobra species. To determine the unique distribution of snake venom phospholipases A2 (svPLA2) in the cobras, the svPLA2 activities for 15 cobra species were examined with an acidimetric and a colorimetric assay, using egg yolk suspension and 4-nitro-3-octanoyloxy benzoic acid (NOBA) as the substrate. The colorimetric assay showed significant correlation between svPLA2 enzymatic activities with the svPLA2 protein abundances in venoms. High svPLA2 activities were observed in the venoms of Asiatic spitting cobras (Naja sputatrix, Naja sumatrana) and moderate activities in Asiatic non-spitters (Naja naja, Naja atra, Naja kaouthia), African spitters (subgenus Afronaja), and forest cobra (subgenus Boulengerina). African non-spitting cobras of subgenus Uraeus (Naja haje, Naja annulifera, Naja nivea, Naja senegalensis) showed exceptionally low svPLA2 enzymatic activities. The negligible PLA2 activity in Uraeus cobra venoms implies that PLA2 may not be ubiquitous in all snake venoms. The svPLA2 in cobra envenoming varies depending on the cobra species. This may potentially influence the efficacy of cobra antivenom in specific use for venom neutralization. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.